Analysis characteristic of cholesteryl acrylate conductivity with the addition of the PE-b-PEG doped ITO-nanoparticle in the development of liquid crystal technology. Issue 1 (May 2020) - Ismail, M; Afrizal, A; Syafei, D I; Puspita, M A
Abstract: The study of liquid crystal material is very interesting and has the opportunity as a smart material such as cholesteryl acrylate. Liquid crystal cholesteryl acrylate can be made shynthesized by Acryloiloxy Butyloxy Benzoate (ABB) precursor and cholesterol. Cholesteryl acrylate was polymerized by the ultraviolet curing (UV-Curing) method to keep the crystal structure stable. During the polymerization process some ingredients are added which can increase and regulate the formation of liquid crystal structure phases. Cholesteryl acrylate can be doped by adding conductive oxide in the form of nano particle scale Indium Tin Oxide (18 nm). The optimum conductivity results were 5.70 × 10 −7 S/m with the addition of ITO 10% w/w. The structure of the crystal phase formed can be directed by the addition of Polyethylene-block-Polyethylene Glycol during the UV-Curing process. The hydrophobic part of PE block will interact with hydrophobic liquid crystal molecules, while the hydrophilic part of the PEG block has a high affinity for the hydrophilic ITO electrode substrate. The added PE-b-PEG varies from 0.001 to 0.005 percent by weight of polymer cholesteryl acrylate composite. Conductance data is measured using LCR meters from a frequency of 50 Hertz to 5000 kHertz. The average conductance data for ITO is 0.09597838 S, cholesteryl acrylate is 5.20635 × 10 −6 S, the polymer cholesteryl acrylate composite with doped ITO is 4.58284 × 10 −6 S. When added PE-b-PEG 0, 003 percent composite weight is obtained the highest average conductance data is 1.24234 × 10 −5 S with an average conductivity value of 6.09 × 10 −5 S/m. The varies composition of PE-b-PEG content is very influential to regulate the arrangement of crystals formed in electrical conductivity.